2016
DOI: 10.1111/jan.13061
|View full text |Cite
|
Sign up to set email alerts
|

A path analysis of stress and premenstrual symptoms in Korean international and Korean domestic students

Abstract: This study proposes a revised conceptual model that will contribute to the understanding of stress and premenstrual symptom severity in women in the acculturation process and concludes with suggestions and implications for future nursing practice and research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 87 publications
1
7
0
Order By: Relevance
“…The items are rated on a 7-point Likert system. The reliability of the translated Korean version of MSPSS was tested in a previous study of Korean female college students and had a Cronbach’s alpha of 0.81.27 In this study, the Cronbach’s alpha was 0.95.…”
Section: Methodsmentioning
confidence: 93%
See 1 more Smart Citation
“…The items are rated on a 7-point Likert system. The reliability of the translated Korean version of MSPSS was tested in a previous study of Korean female college students and had a Cronbach’s alpha of 0.81.27 In this study, the Cronbach’s alpha was 0.95.…”
Section: Methodsmentioning
confidence: 93%
“…To examine the extent to which the illness perception and sense of well-being are related and to explore the role of perceived social support in the relationship, structural equation modeling (SEM) was performed using Mplus 7.4. The SEM was performed in two models: model 1 using the sum scores of the total IPQ-R and model 2 using the sum scores on the IPQ-R subscales: “negative illness perception” and “positive illness perception.” The criteria applied to evaluate the adequate model fit of this study were comparative fit index (CFI)>0.95, root mean square error of approximation (RMSEA)<0.60, and standardized root mean square residual (SRMR)<0.80 27,33. The study used sum scores of MSPSS and FACT-B because the model fit was inadequate when using the subscales of these instruments ( X 2 =949.942, df =3, p <0.001, RMSEA=0.00, CFI=1.00, SRMR=0.00).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies indicate that social jetlag (Taillard et al, 2021), obesity (Speed et al, 2019), premenstrual symptoms (Y. Lee & Im, 2016), chronotype (Walsh et al, 2022), and sleep quality (Jeong & Min, 2021) are associated with depression. Thus, all the above variables were included in this study.…”
Section: Methodsmentioning
confidence: 99%
“…These results are congruent with previous findings of a negative association between symptoms’ severity and patient care [ 28 ]. Other studies also observed an association between professional responsibility and menstrual symptoms’ severity [ 29 , 30 ]. For nurses in group 2 who had relatively severe menstrual symptoms, support for relief from physical symptoms would help reduce deficiency of professional function.…”
Section: Discussionmentioning
confidence: 71%